국가슈퍼컴퓨팅 생태계 활성화를 위한 법제도 개선방안 - 허태상(Taesang Huh); 정용환(Yonghwan Jung); 고명주(Myoungju Koh) (한국콘텐츠학회 논문지, 21(2), 2021)
Supercomputers have played an important role in various fields such as science, industry, national security and solutions for social issues, and their demand is increasing significantly as their use is strengthened in areas using big data and AI. Recently, competition for global exascale system development is accelerating based on various architectures, and the era of exascale computing is expected to come in the near future. However, the foundation of the domestic supercomputing ecosystem was lost due to the decline of the server industry in the past, and although the related law was enacted to supplement and foster it, it has not been able to perform its function smoothly. Therefore, this article examines the problems in the current legal system through the analysis of the relevant legal system and the status of the supercomputing ecosystem, and suggests improvements so that the relevant legal system, which can accommodate the reinforcement of the role of the government·national center·professional center, support for industries, promotion of commercialization of research results, and flexibility of government promotion policies, can prepare the basis for the promotion of the supercomputing R&D project. 슈퍼컴퓨터는 과학, 산업, 국가안보 및 사회현안 해결 등의 다양한 분야에서 중요한 역할을 수행해 왔으며, 빅데이터, AI 등을 활용한 영역에서의 활용이 강화되면서 그 수요는 크게 증가하고 있다. 최근에는 다양한 아키텍처 기반으로 글로벌 엑사스케일 시스템 개발 경쟁이 가속화되고 있어, 머지않은 미래에 엑사스케일 컴퓨팅 시대가 도래할 예정이다. 그러나, 국내 슈퍼컴퓨팅 생태계는 과거 서버산업 쇠퇴로 기반이 유실되었으며, 이를 보완 및 육성하고자 관련 법이 제정되었음에도 그 기능을 원활히 수행하지 못하고 있다. 이에 본 연구에서는 유관 법제도 분석 및 슈퍼컴퓨팅 생태계 현황 분석을 통해 현행 법제도에서의 문제점을 살펴보고, 정부·국가센터·전문센터의 역할 강화, 산업체 지원, 연구결과의 실용화 촉진, 정부 육성시책의 유연성을 수용하고 연관 법제도에서 슈퍼컴퓨팅 연구개발사업의 추진 근거를 마련할 수 있도록 개선사항을 제시한다.